FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN LAPORAN KEUANGAN - Mulia Alim; Ida Ida (JMB : Jurnal Manajemen dan Bisnis, 2018)
In the quality of financial information there are two types of disclosure issued by the company. The disclosure is mandatory disclosure is a mandatory disclosure of government regulation and voluntary disclosure is an unregulated disclosure. The purpose of this study to determine the effect of ROA, Leverage and size of the company on the disclosure of financial statements. The disclosure categories used in this study were Mandatory Disclosure categories by taking a sample of 9 companies after deducting from the specified sample criteria. Data analysis method used is panel data regression analysis.